Homeotic change in segment identity derives the human vertebral formula from a chimpanzee‐like one. Issue 2 (6th July 2021) - Williams, Scott A.; Pilbeam, David
Abstract: Objectives: One of the most contentious issues in paleoanthropology is the nature of the last common ancestor of humans and our closest living relatives, chimpanzees and bonobos (panins). The numerical composition of the vertebral column has featured prominently, with multiple models predicting distinct patterns of evolution and contexts from which bipedalism evolved. Here, we study total numbers of vertebrae from a large sample of hominoids to quantify variation in and patterns of regional and total numbers of vertebrae in hominoids. Materials and Methods: We compile and study a large sample (N = 893) of hominoid vertebral formulae (numbers of cervical, thoracic, lumbar, sacral, caudal segments in each specimen) and analyze full vertebral formulae, total numbers of vertebrae, and super‐regional numbers of vertebrae: presacral (cervical, thoracic, lumbar) vertebrae and sacrococcygeal vertebrae. We quantify within‐ and between‐taxon variation using heterogeneity and similarity measures derived from population genetics. Results: We find that humans are most similar to African apes in total and super‐regional numbers of vertebrae. Additionally, our analyses demonstrate that selection for bipedalism reduced variation in numbers of vertebrae relative to other hominoids. Discussion: The only proposed ancestral vertebral configuration for the last common ancestor of hominins and panins that is consistent with our results is the modal formula demonstrated by chimpanzees and bonobos (7 cervical‐13 thoracic‐4 lumbar‐6 sacral‐3 coccygeal). H ox gene expression boundaries suggest that a rostral shift in Hox10/Hox11 ‐mediated complexes could produce the human modal formula from the proposal ancestral and panin modal formula. Abstract :